From Paper to Tablets: Digitalizing Exams - Chabokdavan, Mona; Frattini, Gabriele; Kuang, Junyi; Lindfors, Oscar; Lübeck, Viktor; Stein, Natalie (My University, 2025)
The increasing digitalization of education has highlighted the limitations of traditional paper-based exams, particularly regarding efficiency, security, and sustainability. Existing digital exam platforms, such as Inspera, often fall short in subjects requiring sketches, formulas, or structured formatting. This thesis addresses the need for a more flexible solution with improved usability that supports both students and teachers. The aim of the project is to further develop a digital exam application for Android tablets that enables both freehand drawing and structured text input. Building on a previous project, this work focuses on improving usability and strengthening security, with the overall goal of reducing administrative workload and enhancing the exam experience. Through usability testing, key usability challenges and security concerns were identified and addressed. New features such as a lasso tool, recovery codes, automatic submission, and time-restricted access were implemented to meet these needs. While participants generally found the interface intuitive, some aspects such as switching between drawing and scrolling require further refinement. The final prototype combines core exam functionality with a clean and efficient interface. Results indicate that tablet-based exam systems can improve flexibility, accessibility, and user experience. Future development should explore accessibility adaptations and integration with external administrative systems.
Keywords: Digital exam platforms; Usability; Security; Android tablets; Structured text input; Freehand drawing